Speech Disorder in Children: Stuttering Disfluency in Selected Video - Muhamad Sandi Alfikri; Tryana Tryana; Rizky Tazkiyatul Ummami; Maharanny Setiawan Poetri; Denok Sunarsi (International Journal of Education, Information Technology, and Others, 2022)
This study aims to present language disorder that is happened in stuttering symptoms in human language and speech. This study uses qualitative method that collects the data from selected YouTube video entitled Stuttering: For Kids, By Kids and other sources from books that are selected from some theories. The object of the study is in English that provides some children who have stuttering in their speaking skill